Evaluación del desempeño del recubrimiento nanoestructurado de ZrN-Si sobre acero inoxidable 316L mediante técnicas electroquímicas (2022)
Nanostructured coatings have been widely used by industry to improve the surface properties of materials. Among the most widely used coatings are transition metal nitrides with added silicon. These materials in the form of coatings have shown very good physical and chemical properties. In this work, the effect of silicon (Si) incorporation on the chemical composition, microstructure and corrosion resistance of zirconium nitride (ZrN) coatings with different silicon contents was investigated. The elemental chemical composition was obtained by energy dispersive X-ray spectroscopy (EDS) technique and the results showed that the atomic content of silicon in the coatings was increasing as a function of silicon pellets: for one silicon pellet 6 at.%, two pellets 11 at.% and three pellets 21 at.%. The microstructure of the samples was studied by X-ray diffraction technique (XRD). For the coating with a silicon atomic content of 0.0 at.%., the presence of a ZrN nanocrystalline phase with an fcc structure was observed. However, with the incorporation of silicon, the diffraction peaks were broad and of lower intensity, which is related to the formation of an amorphous Si3N4 phase and a decrease in the size of the ZrN crystallite. The functionality of the ZrN-Si coatings was evaluated from corrosion tests, using electrochemical techniques of potentiodynamic polarization and electrochemical impedance spectroscopy through equivalent electrical circuit fitting. The results showed that as the atomic content of silicon in the ZrN coating increased, the performance in the saline medium improved due to the formation of an amorphous Si3N4 phase that does not allow the diffusion of the electrolyte towards the substrate. Therefore, these coatings have potential applications as protective coatings.